Analisis Pengembangan Kurikulum Pendidikan Agama Islam dalam Perspektif Outcome-Based Education di MAN 2 Kota Sukabumi - Rahmat, Mila Kamila; Nugraha, Mulyawan Safwandy (CV. Berkah Cakrawala Inspirasi, 2026)
This study aims to examine the development of the Islamic Religious Education (PAI) curriculum from the perspective of Outcome-Based Education (OBE) at MAN 2 Sukabumi City. This research employed a qualitative approach with a case study design. Data were collected through classroom observations, semi-structured interviews with the vice principal for curriculum affairs, PAI teachers, and students, as well as document analysis of syllabi, teaching modules, and assessment instruments. The findings reveal that the PAI curriculum at MAN 2 Sukabumi City has implicitly integrated OBE principles, including clearly formulated learning objectives, the implementation of active learning methods, religious practices as indicators of competency achievement, and authentic assessment covering cognitive, affective, and psychomotor domains. However, the implementation of OBE has not yet been fully formalized and still faces challenges, such as limited instructional time and the uneven understanding of OBE concepts among teachers. This study contributes to the transformation of the PAI curriculum toward competency-based learning in the context of Islamic senior high schools (madrasah aliyah).